INTERACTION BETWEEN INFORMATION COMPLEXES IN ECONOMIC SPHERES (Conference Zone, 2022)
The stage of development of modern civilization is the stage of transition to an informed society. The concept of an informed society emerged in the second half of the 1960s as part of an improvement in the concept of a post-industrial society. In today's post-industrial economies, which are typical of most developed countries, the emphasis is on providing services rather than producing goods. The growing role of information and knowledge in the information society, the increase in the share of information communication, information products and services in GDP, the creation of a global information space that allows people to interact effectively through information, their access to global information resources and information products and services characterized by the degree to which their social and personal needs are met